2007
DOI: 10.1557/jmr.2007.0163
|View full text |Cite
|
Sign up to set email alerts
|

Processing of yttrium-doped barium zirconate for high proton conductivity

Abstract: The factors governing the transport properties of yttrium-doped barium zirconate (BYZ) have been explored, with the aim of attaining reproducible proton conductivity in well-densified samples. It was found that a small initial particle size (50-100 nm) and high-temperature sintering (1600°C) in the presence of excess barium were essential. By this procedure, BaZr 0.8 Y 0.2 O 3−␦ with 93% to 99% theoretical density and total (bulk plus grain boundary) conductivity of 7.9 × 10 −3 S/cm at 600°C [as measured by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
304
4
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(348 citation statements)
references
References 28 publications
31
304
4
9
Order By: Relevance
“…8). The shape and size of the semicircle did not depend on electrode polarization, which indicates that the processes characterized by this semicircle do not take place in Pt electrode and in three phase boundary of Pt electrode, gas phase and electrolyte and as accepted in literature 21 are characteristic for processes at grain boundary interfaces and bulk phase (Fig. 8).…”
Section: Preparation Of Protective Bazrsupporting
confidence: 60%
See 1 more Smart Citation
“…8). The shape and size of the semicircle did not depend on electrode polarization, which indicates that the processes characterized by this semicircle do not take place in Pt electrode and in three phase boundary of Pt electrode, gas phase and electrolyte and as accepted in literature 21 are characteristic for processes at grain boundary interfaces and bulk phase (Fig. 8).…”
Section: Preparation Of Protective Bazrsupporting
confidence: 60%
“…Grain boundary resistance R gb was obtained by subtraction of R bulk from R tot value. The characteristic frequencies of high frequency semicircles were typical for grain boundary processes in HTPC 21 and varied from 10 kHz to 250 kHz in studied temperature range (550…”
Section: Preparation Of Protective Bazrmentioning
confidence: 99%
“…The electrical conductivity of the BZY_ZnO electrolyte was two to five times higher than that observed for the BZY electrolyte under the same conditions, which is due to its higher relative density. This result is in good agreement with data reported by Haile et al 17,20 In contrast, the BZY_ZnO_H 3 PO 4 electrolyte showed the lowest electrical conductivity, especially at temperatures above 300…”
Section: Resultssupporting
confidence: 93%
“…The most promising proton conducting electrolytes are BaCe1-xYxO3-x/2 (BCY) 4,[8][9][10][11] and BaZr1-xYxO3-x/2 (BZY), [12][13][14][15][16] which exhibit high proton conductivity at intermediate temperatures (~500 C) 17 . Despite the encouraging proton conductivity of these materials, there are several issues addressed related to their chemical stability, mechanical properties and difficulties in sintering of BZY.…”
Section: -7mentioning
confidence: 99%